Formative and Summative Assessment Using Technology: A Critical Review - Onasanya , Samuel Adebisi; Ajamu, Adesoye Oladunni (Universitas Pendidikan Ganesha, 2024)
The use of technology in the classroom has revolutionized the teaching process by giving educators more freedom and opportunities to differentiate instruction. The purpose of this research is to critically assess a variety of technological approaches that were particularly chosen for their compatibility with and ability to improve on existing assessment for learning practices. The underlying viewpoints are that (a) summative and formative evaluations are both important learning opportunities, and (b) utilizing technology can improve learning throughout evaluation and feedback processes. The research method uses Systematic Literature Review (SLR). A literature search was conducted through academic databases, such as PubMed, ERIC, and Google Scholar. The benefits and downsides of employing technology are evaluated using research from a research study through literature. It is said that the usage of various forms of technology can aid in the facilitation of efficient assessment for learning and feedback in higher education by adopting a flexible strategy and taking tiny incremental steps. In a supportive learning environment, where a staff-student approach can be particularly helpful, trust between students and staff can help innovative methods succeed.